2016
DOI: 10.1039/c5tc03769g
|View full text |Cite
|
Sign up to set email alerts
|

Electron-transporting third component modifying cathode for simplified inverted ternary blend solar cells

Abstract: Electron transporting materials widely used in organic light-emitting diodes, such as Bphen, BCP and TPBI, are used as a third component to serve as a cathode buffer layer for fabricating simplified inverted ternary blend polymer solar cells without an additional cathode-modifying interlayer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…For ternary PSCs, it has been reported that the vertical distribution of the third component introduced into the binary photoactive layer is crucial for its role in the device. 39 To probe the vertical distribution of C 60 -IMZ within the P3HT:PC 61 BM photoactive layer film, we carried out XPS measurements in combination with the depth profile analysis. To overcome the depth detection limit of our commercial XPS instrument, which is only around 10 nm, we combined the manual argon ion beam etching with XPS analysis so as to obtain two depth profiles (top and near-bottom layers) of the ternary photoactive layer film with 10 wt % C 60 -IMZ.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For ternary PSCs, it has been reported that the vertical distribution of the third component introduced into the binary photoactive layer is crucial for its role in the device. 39 To probe the vertical distribution of C 60 -IMZ within the P3HT:PC 61 BM photoactive layer film, we carried out XPS measurements in combination with the depth profile analysis. To overcome the depth detection limit of our commercial XPS instrument, which is only around 10 nm, we combined the manual argon ion beam etching with XPS analysis so as to obtain two depth profiles (top and near-bottom layers) of the ternary photoactive layer film with 10 wt % C 60 -IMZ.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In recent years, ternary PSCs, which are characteristic in the involvement of a third component in the binary photoactive layer, appear as a novel structure with the possibility of improving all photovoltaic parameters simultaneously. The involved third component of ternary PSCs may function either as the additional donor/acceptor participating in the charge/energy transfer process or as highly soluble thermal precursor fullerenes/polymers transferable to target donor/acceptors. In particular, the third component may serve as a self-assembled interfacial layer facilitating charge transport at the interface, and in this case the ternary PSCs incorporating as the third component as a self-assembled interfacial layer are advantageous in simplifying the device structure relative to the conventional binary PSCs containing the interfacial layer incorporated via an additional fabrication step. So far, such reported third components functioning as a self-assembled interfacial layer in ternary PSCs include fullerene derivatives, conjugated or nonconjugated polymers, surfactant, and π-conjugated small molecules. Among them, because of the strong electron-accepting ability and the structural similarity to the widely used fullerene acceptors in the conventional binary PSCs, fullerene derivatives are suitable candidates of the third components of ternary PSCs, and a few reports revealed that fullerene derivatives incorporated as the third component of the ternary PSCs were indeed able to self-assemble at the photoactive layer/cathode interface and consequently facilitated charge transport at such an interface. However, reports on applying fullerene derivatives as the third component of the ternary PSCs in inverted configuration, which is more promising than the regular-structure PSCs because of the higher ambient stability, are quite few. , For instance, in 2014, Chen and co-workers synthesized an amine-based [6,6]-phenyl-C 61 -butyric acid 2-((2-(dimethylamino)­ethyl) (methyl)-amino)-ethyl ester (PCBDAN), and doped it into the poly­(3-hexylthiophene-2,5-diyl:[6,6]-phenyl C 61 -butyric acid methyl ester (P3HT:PC 61 BM) photoactive layer, and achieved a dramatic PCE enhancement for the inverted ternary PSCs, which was attributed to the self-organization of PCBDAN leading to its enrichment on buried ITO surface and consequently reduced ITO’s work function . More recently, Andersson et al added pyridine- and amine-functionalized PC 61 BM into an active layer blend c...…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] Zhang's group reported a record PCE value of over 16% by using ternary films as the photoactive layer. [27] Notably, several excellent groups, such as Brabec's group, [28] Yang's group, [29] Thompson's group, [30] Cao's group, [31] Zhan's group, [32] and Hou's group, [33] have summarized the progress in ternary PSCs. According to the previous reports, three high photovoltaic parameters can hardly be simultaneously achieved in one binary PSC, which is limited by the intrinsic properties of the used materials.…”
Section: Introductionmentioning
confidence: 99%
“…The solid-state isothioureas are characterized by a surrounding electron density capable to participate in hydrogen bonds with indium tin oxide substrates. , In general, the H-bonding ability of thioureas remains in the solid state for small molecules (2010 Li) and also in polycyclic frameworks with one or more urea/thiourea fragments …”
Section: Introductionmentioning
confidence: 99%
“…55 The solid-state isothioureas are characterized by a surrounding electron density capable to participate in hydrogen bonds with indium tin oxide substrates. 56,57 In general, the H-bonding ability of thioureas remains in the solid state for small molecules (2010 Li) 53 and also in polycyclic frameworks with one or more urea/thiourea fragments. 58 In our previous study, diluted solutions of isothiouronium polythiophenes were characterized using steady-state absorption and fluorescence by changing alkoxy-spacer length and solvent.…”
Section: ■ Introductionmentioning
confidence: 99%